Analisis Komunikasi Interpersonal dalam Memperkuat Kepercayaan dan Syura Antar Pengusaha Syariah di Komunitas Pesantren - Muhamad Hanif Fuadi; Sabiq Syahid Muslim; Ridwanulloh; Santi Setiawati (CV Kalimasada Group, 2025)
This study analyzes the role of interpersonal communication in strengthening the principles of amanah (trust) and shura (deliberation) among Islamic boarding school-based sharia entrepreneurs. The case study was conducted at the Miftahul Ulum Gandok Islamic Boarding School Cooperative, Tasikmalaya, with a focus on the dynamics of internal communication, shura practices in business decision-making, and the value of ukhuwah (brotherhood) as the foundation of collective business. The research method uses a qualitative approach with data collection techniques through in-depth interviews, participatory observations, and document studies. The results of the study show that: (1) Open and egalitarian interpersonal communication facilitates transparency (trust) in cooperative financial management; (2) Shura forums function as a medium for conflict resolution and business innovation; (3) The value of ukhuwah strengthens the cohesiveness of members in facing market challenges. These findings contribute to sharia business literacy based on the values of the pesantren community.